Calibração de redes de distribuição de água pelo método inverso aplicado a escoamento transiente - Araújo, John Kenedy de (2003)
A method for estimation of parameters of existing hydraulic networks on the basis of observed transients pressures. Such parameters include pipe friction factors or absolute roughness, their diameters and the leakage locations and discharges. The inverse transient problem in terms of unknown parameters is solved through an indirect calibration procedure, which compares the calculated and observed hydraulic heads. The search method for optimal parameters employs the Method of Characteristics for the solution equations of transient motions in pipes and Genetic Algorithms. The initial conditions in the state of equilibrium are supposed unknown and the observed transient behavior of the network is in response to a valve maneuver composed of partial closure and reestablishment of flow in a pipe. In order to validade the transient calibration method, an example network is used to test various proposed calibration problems. The results show that the proposed method can be used with confidence for determination of various kinds of parameters. The transient inverse method is capable of network calibration using transient data collected at few locations in response to a quick valve maneuver.